Depleting State of Medicinal Plants in Rajasthan (India) and their Conservation - Billore, K. V. (Indian Forester, 2000)
India is one of the rich countries in the world as far as the natural resources are concerned. The vast land of Rajasthan together with its vegetation and flora has a variety of medicinal plants growing in different habitats. However, over all developmental activities, mechanization of life and over exploitation of natural resources and change in enviornment during last one and a half decade has brought about a substaintial depletion in the forests of the state in general and the medicinal plants in particular. As a result of which well know medicinal plants like Guggulu, Shatawari, Ashwagandha, Gorakhmundi, Shallaki, Bhringaraj etc. Which used to be abundant in nature have now become endangered and rare. In the present paper an account of the dwindling resources of 25 medicinal plants have been together with possible measures for their conservation in the state.